NEW FINDS OF FOSSIL HAMAMELIDS AND DATA ON THE PHYLOGENETIC RELATIONSHIPS BETWEEN THE PLATANACEAE AND HAMAMELIDACEAE - Maslova N.P.; Herman A.B. (My University, 2004)
Pistillate heads of Anadyticarpa altingiosimila gen. et sp. nov. from the Late Albian-Early Cenomanian of northeastern Russia are assigned to the Hamamelidaceae (Altingioideae) on the basis of their microstructure. The heads were found in association with leaves of "Platanus" louravetlanica Herman et Shezepetov and bark impressions. The phylogenetic relationships between the Platanaceae and Hamamelidaceae are discussed.
Keywords: reproductive structures; leaf and bark remains; Hamamelidaceae; Platanaceae; phylogeny; early angiosperms; Mesozoic::Cretaceous::Upper::Cenomanian; Mesozoic::Cretaceous::Lower::Albian; Мезозой::Меловая::Верхний::Сеноманский; Мезозой::Меловая::Нижний::Альбский